Resolution of complete heart block after revascularization of acute marginal branch of the right coronary artery - Oluwaseyi Bolorunduro; Rami N Khouzam; Dwight Dishmon (KARE Publishing, 2014)
A patient presented with typical angina and a non-ST elevation myocardial infarction. Electrocardiogram showed complete heart block, and she was found to have a 90% acute marginal artery stenosis. The block resolved after balloon angioplasty of this artery that does not supply the atrioventricular node. We propose that increased vagal tone due to inferior wall ischemia from acute marginal artery stenosis has elicited the Bezold-Jarisch reflex. This is a likely mechanism for this uncommon etiology of complete heart block.